Investigation of Mechanical Properties of Polymer Coatings on Surfaces - et. al., Thant Zin Hein, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work, the mechanical properties of organic coatings based on epoxy resin (DGEBA DER 332) and two diamines comonomers (IPD and 3DCM) on the surface of aluminum and titanium alloy plates were investigated. It has been proven that Young's modulus and internal residual stress of coatings depend on the thickness of the coating, the degree of reaction and the substrate material. During the thermal cure cycle, a loss of curing agent was observed and thus a change in the degree of reaction of the coating. The results showed that Young's modulus and stress of thin coatings are very different from volumetric values.